Stable Isotope Tracing Uncovers Reduced γ/β-ATP Turnover and Metabolic Flux Through Mitochondrial-Linked Phosphotransfer Circuits in Aggressive Breast Cancer Cells - Klepinin, Aleksandr; Miller, Sten; Reile, Indrek; Puurand, Marju; Rebane-Klemm, Egle; Klepinina, Ljudmila; Vija, Heiki; Zhang, Song; Terzic, Andre; Dzeja, Petras; Kaambre, Tuuli (Frontiers in Oncology, 2022)
Changes in dynamics of ATP γ- and β-phosphoryl turnover and metabolic flux through phosphotransfer pathways in cancer cells are still unknown. Using 18O phosphometabolite tagging technology, we have discovered phosphotransfer dynamics in three breast cancer cell lines: MCF7 (non-aggressive), MDA-MB-231 (aggressive), and MCF10A (control). Contrary to high intracellular ATP levels, the 18O labeling method revealed a decreased γ- and β-ATP turnover in both breast cancer cells, compared to control. Lower β-ATP[18O] turnover indicates decreased adenylate kinase flux. Aggressive cancer cells had also reduced fluxes through hexokinase G-6-P[18O], creatine kinase [CrP[18O], and mitochondrial G-3-P[18O] substrate shuttle. Decreased CK metabolic flux was linked to the downregulation of mitochondrial MTCK1A in breast cancer cells. Despite the decreased overall phosphoryl flux, overexpression of HK2, AK2, and AK6 isoforms within cell compartments could promote aggressive breast cancer growth. Here we proposed that AK2 and AK6 is novel metabolic targets for aggressive triple-negative breast cancer.